2020
DOI: 10.1038/s41598-020-63733-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel HNF1B mRNA splicing variants and their qualitative and semi-quantitative profile in selected healthy and tumour tissues

Abstract: Hepatocyte nuclear factor-1-beta (HNF1B) is a transcription factor crucial for the development of several tissues, and a promising biomarker of certain solid tumours. Thus far, two HNF1B alternative splicing variants (ASVs) have been described, however, the complete spectrum, prevalence and role of HNF1B ASVs in tumorigenesis are unclear. Considering the equivocal data about HNF1B ASVs and expression presented in literature, our aim was to characterize the spectrum of HNF1B mRNA splicing variants across differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…One of the possible explanations for this difference may lie in to the fact that the expression on a protein level and mRNA level may be difficult to correlate for several reasons including translation rates, translation rates modulations, modulations of protein half-life, protein synthesis delay, and protein transport 55 . Moreover, in our recent study, we have shown that there are several transcriptional variants of HNF1B which have not been recognized yet (contrary to the previous knowledge about three possible HNF1B isoforms) 56 . The positive correlation between HNF1B and EZH2 expression in our study was also reflected in the observed positive correlation between AR expression and expression of both EZH2 and HNF1B.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…One of the possible explanations for this difference may lie in to the fact that the expression on a protein level and mRNA level may be difficult to correlate for several reasons including translation rates, translation rates modulations, modulations of protein half-life, protein synthesis delay, and protein transport 55 . Moreover, in our recent study, we have shown that there are several transcriptional variants of HNF1B which have not been recognized yet (contrary to the previous knowledge about three possible HNF1B isoforms) 56 . The positive correlation between HNF1B and EZH2 expression in our study was also reflected in the observed positive correlation between AR expression and expression of both EZH2 and HNF1B.…”
Section: Discussioncontrasting
confidence: 67%
“…After RNA quality characterization, 3.75 µg of the total RNA of each sample (where available) was treated by DNase I (Thermo Fisher) prior to one-step cDNA synthesis in 40 µl reaction using SuperScript III Reverse Transcriptase (Thermo Fisher) with random hexamers (Roche) as described previously 56 . All RNA samples were processed according to the Digital MIQE Guidelines 65 .…”
Section: Methodsmentioning
confidence: 99%
“…Normalized NGS data (ratio of individual splicing reads) showed a similar relative expression of the studied variants when compared to ddPCR quantitative analysis (Table 3 ). Moreover, we did not identify any novel HNF1B splicing variants by capture RNA-Seq other than those reported in our previously published work, where deep sequencing of individual HNF1B exon-exon junctions was used, which could potentially miss the ASVs 19 .
Figure 5 Representative example of the HNF1B splicing pattern based on the capture RNA-Seq of a kidney T sample visualised as a sashimi plot in IGV (Broad Institute).
…”
Section: Resultsmentioning
confidence: 76%
“…The HNF1B reference transcript comprises nine coding exons and produces full length 557 amino acid protein (RefSeq NM_000458). In our previous work, we performed mainly qualitative analyses and described 45 splicing events in a limited number of samples (eight representative samples per analysed tissue pool) 19 . By this approach we have identified predominant and predominant-candidate HNF1B ASVs (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation